Produtividade, eficiência energética e econômica em semeadura cruzada de soja - Riquetti, Neilor Bugoni [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
A cultura da soja é de grande importância social e econômica, pois além de gerar receitas para o país gera inúmeros empregos em diversos setores da agricultura, indústria e transportes. Buscando maior retorno financeiro, diversos métodos de cultivo são testados e estudados por produtores e pesquisadores com objetivo de elevar a produtividade da lavoura, através da modificação do arranjo das plantas na área, entre as quais a semeadura em linhas cruzadas se tornou objeto de estudo. Durante o ciclo da cultura várias operações são necessárias, iniciando com a dessecação da área, semeadura, tratos culturais, colheita e transporte dos grãos. Todas essas atividades exigem determinada quantidade de energia e investimento financeiro para sua realização. Observando-se a crescente preocupação com o uso racional de energia e a obtenção de um retorno financeiro elevado, este trabalho teve como objetivo avaliar o balanço energético e econômico do cultivo da soja em semeadura cruzada no sistema de plantio direto, assim como avaliar as características agronômicas das plantas. O experimento foi realizado na Fazenda São Luiz localizada no município de Primavera do Leste – MT. O delineamento experimental foi de blocos casualizados com 5 repetições contendo os seguintes tratamentos: semeadura em linhas paralelas com 200 kg ha-1 do formulado 11-45-00 e 360000 sementes ha-1; semeadura cruzada com 400 kg ha-1 do formulado 11-45-00 e 720000 sementes ha-1; semeadura cruzada com 7200000 sementes ha-1 e 200 kg ha-1 do formulado 11-45-00; semeadura cruzada com 360000 sementes ha-1 e 400 kg ha-1 do formulado 11-45-00; semeadura cruzada com 200 kg ha-1 do formulado 11-45-00 e 360000 sementes ha-1. As ...

Soybean cultivation is of great social and economic importance, because besides generating revenues for the country, it generates countless jobs in agriculture, industry and transportation. Seeking better financial prospects, many cultivation methods are tested and studied by producers and researchers, with the aim of raising crop productivity, through modifications of plant arrangements in the area, among which cross-seeding, our study subject. Various operations are needed during cultivation cycles, starting with soil exsiccation, seeding, cultivation, harvesting and grain transportation. All of those activities require a determined amount of energy and financial investment for their fulfillment. Observing the rising concern with rational use of energy and the achievement of high revenues, this work had as objective evaluating the energetic and economic balance of soybean cultivation in cross-seeding using the tillage system, as well as assessing the agronomical characteristics of the plants. The experience was carried out at Fazenda São Luíz, located in Primavera do Leste – MT. The experimental delimitation was of randomized blocks with five repetitions containing the following treatments: parallel-line seeding with 200 kg ha-1 of formulated 11-45-00 and 360000 seeds ha-1; cross-seeding with 400 kg ha-1 of formulated 11-45-00 and 720000 seeds ha-1; cross-seeding with 7200000 seeds ha-1 and 200 kg ha-1 of formulated 11-45-00; cross-seeding with 360000 seeds and 400 kg ha-1 of formulated 11-45-00; cross-seeding with 200 kg ha-1 of formulated 11-45-00 and 360000 seeds ha-1. The evaluated agronomical characteristics were: plant height, and from the insertion of the first pod, thousand-grain mass and productivity. The quantification of roads and energy was accomplished through the sum of the built-in energy referring to the inputs used during cultivation added to the energetic depreciation of the ...
Productivity, energetic and economic efficiency in soybean cross-seeding
Keywords: Cultivos agricolas energeticos; Soja - Semeadura; Produtividade agrícola; Viabilidade economica; Soja